P072 The involvement of extracellular Nicotinamide Phosphoribosyltransferase (eNAMPT) and Nicotinate Phosphoribosyltransferase (eNAPRT) in inflammatory bowel disease. (27th May 2021) - Colombo, G; Ribaldone, D G; Caviglia, G P; Genazzani, A; Travelli, C
Abstract: Background: Nicotinamide phosphoribosyltrasferase (NAMPT) is a pleiotropic enzyme which catalyses the first and rate-limiting step in the biosynthesis of NAD. It is present in two different forms: an intracellular form, called iNAMPT, (Chiarugi et al., 2012), and an extracellular form, eNAMPT. eNAMPT is considered an important factor for granulocyte-colony stimulating factor-(G-CSF)-induced myeloid differentiation, with paracrine and autocrine effects on different cell types ( i.e. immune and cancer cells), binding TLR4. NAMPT is structurally and functionally related to the enzyme nicotinate phosphoribosyltransferase (iNAPRT), which is rate-limiting in the NAD salvage pathway that starts from nicotinic acid. The NAD biosynthetic pathways controlled by NAMPT and NAPRT are closely interconnected and can compensate for each other. Also, NAPRT is identified as an extracellular ligand (eNAMPRT) for TLR4 and a mediator of inflammation (Managò et al., 2020). Importantly, iNAMPT and eNAMPT levels are increased in several pathologies, included inflammatory bowel disease (IBD). It has been reported that serum eNAMPT levels correlate with the stage of the pathology: in an active state of the disease the levels of NAMPT are very high, however its levels are partially reduced in a remission stage (Moschen et al., 2007). Methods: First, we investigated the role of eNAMPT and eNAPRT in murine IBD models (especially in DNBS and DSS model). We took into account phenotypic effect as weight loss and colon shortening, but also the reduction of mRNA of inflammatory genes with RT-PCR, tissue damage with H&E and IHC analysis and systemic and local production through colon explant. Secondly, we determined serum eNAMPT and eNAPRT levels in a cohort of adult IBD patients. Results: Both eNAMPT and eNAPRT have been found elevated in 180 IBD patients, as proinflammatory marker of the pathologies. These levels are also elevated in serum and colonic explant of DSS and DNBS preclinical models, associated to an active state of the disease, as a pro-inflammatory response developed locally and systemically. Moreover, we performed ELISA analysis on sera of 100 IBD patients, eligible for anti-TNF treatment, both pediatric and adults. Serum eNAMPT levels are increased before the treatment, responsive patients verified a reduction of these levels, while no-responsive ones verified higher levels. Conclusion: eNAMPT and eNAPRT could be considered pro-inflammatory markers of IBD and possible druggable targets.